2008
DOI: 10.1210/jc.2007-2606
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensitivity of Men and Women to Anorexigenic and Memory-Improving Effects of Intranasal Insulin

Abstract: In accordance with animal data, results indicate that men are more sensitive than women to the acute anorexigenic effect of central nervous insulin signaling, whereas insulin's beneficial effect on hippocampus-dependent memory functions is more pronounced in women. Our findings provide support for the notion of a fundamental gender difference in central nervous insulin signaling that pertains to the regulation of energy homeostasis and memory functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
308
5
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 264 publications
(348 citation statements)
references
References 32 publications
31
308
5
4
Order By: Relevance
“…We have previously shown that intranasal insulin administered to young male subjects in the fasted state (Benedict et al, 2008) acutely decreases food intake, and reduces the intake of palatable snacks in young female subjects after lunch . The latter effect concerned post-prandial snacking in the afternoon and likely resulted from effects on reward-processing pathways, which may be assumed to have also played a role in the present experiments, although our study design clearly does not allow for a differentiation between reward-and hunger-related aspects of eating.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We have previously shown that intranasal insulin administered to young male subjects in the fasted state (Benedict et al, 2008) acutely decreases food intake, and reduces the intake of palatable snacks in young female subjects after lunch . The latter effect concerned post-prandial snacking in the afternoon and likely resulted from effects on reward-processing pathways, which may be assumed to have also played a role in the present experiments, although our study design clearly does not allow for a differentiation between reward-and hunger-related aspects of eating.…”
Section: Discussionmentioning
confidence: 99%
“…They were told to abstain from caffeine and to follow their usual dinner routines around 1800-1900 h. Participants arrived at the sleep lab at 2000 h. Adherence to the instructions for the experimental day was confirmed and an intravenous catheter was placed in a vein of the dominant arm. At 2120 h, participants underwent a memory test battery (see Feld et al, 2016, for details and respective results in the group of young subjects) before receiving intranasal insulin or placebo via sixteen 0.1-ml puffs (8 per nostril) in 1-min intervals, amounting to a total dose of 1.6 ml insulin (160 IU) or placebo at 2220 h. This dose was chosen in order to enable comparisons with previous studies on the role of central nervous insulin in the acute regulation of food intake (Benedict et al, 2008;Hallschmid et al, 2012). Subjects went to bed at 2300 h for 8 h of polysomnographically recorded sleep, resulting in an overnight fast of at least 12 h in all subjects.…”
Section: Study Design and Proceduresmentioning
confidence: 99%
See 3 more Smart Citations